21. BANTUAN SEBAGAI INSTRUMEN KEBIJAKAN LUAR NEGERI: KEPENTINGAN DI BALIK BANTUAN PENDIDIKAN AUSTRALIA UNTUK MADRASAH DI INDONESIA, 2011-2015 - Harahap, Sarah Litani; Utomo, Tri Cahyo; Rosyidin, Mohammad (Journal of International Relations, 2016)
Foreign aid as one of the most prominent instrument on foreign policy, defined as nationalinterest by Australia, particularly to protect their national security from any foreign or thirdpartythreats. Australia’s foreign aid began since 2004 to madrasah in Indonesia, after teroristattack happened in five consecutive year (2001-2005) in Indonesia with a target of statehoodAustralian simbolic. It was later found that the terorist group is affiliated with radical Islamicgroup named Jamaah Islamiyah, with madrasah as their educational background. It’s impactedin Australia’s askance point of view on madrasah as a place where Islam radical was taught.Through the Education Sector Support Program (ESSP), given by Australia to 1500 madrasahwich was selected, is not not only to improve madrasah accreditation, but also to proveAustralia’s interest to protecting their nationality.